From deep shape plants to solar cells - Anon (Universiti Malaysia Perlis (UniMAP), 2012)
International Academic Lecture Series: From deep shape plants to solar cells by Prof. Dr. Ali Hussain Reshak, 3rd October 2012 was held at The University Auditorium, Pauh Putra Campus, Perlis, Malaysia.